2000
DOI: 10.1200/jco.2000.18.13.2620
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytosis and the Retinoic Acid Syndrome in Patients With Acute Promyelocytic Leukemia Treated With Arsenic Trioxide

Abstract: Induction therapy of APL with all-trans RA and arsenic trioxide is associated with leukocytosis and the RA syndrome. These clinical effects seem to be intrinsically related to the biologic responsiveness and the differentiation process induced by these new agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(98 citation statements)
references
References 36 publications
1
96
1
Order By: Relevance
“…1 Although the pathogenesis of the syndrome is unclear, laboratory investigations indicate that ATRA promotes inflammatory cytokine generation by APL cells and activates homotypic and heterotypic adhesion, thereby enhancing endovascular permeability and promoting leukemia cell adhesion and transmembrane migration. 2,3 Initially termed the retinoic acid syndrome, subsequent studies revealed that the analogous syndrome may occur in APL patients treated with arsenic trioxide, 4 and rarely in patients with non-promyelocytic subtypes of acute myeloid leukemia treated with ATRA. 5 Lonafarnib (SCH66336 or Sarasart; Schering-Plough Research Institute, Kenilworth, NJ, USA) is a member of a novel class of therapeutics under investigation in hematologic malignancies, termed the farnesyl transferase inhibitors (FTIs).…”
Section: To the Editormentioning
confidence: 99%
“…1 Although the pathogenesis of the syndrome is unclear, laboratory investigations indicate that ATRA promotes inflammatory cytokine generation by APL cells and activates homotypic and heterotypic adhesion, thereby enhancing endovascular permeability and promoting leukemia cell adhesion and transmembrane migration. 2,3 Initially termed the retinoic acid syndrome, subsequent studies revealed that the analogous syndrome may occur in APL patients treated with arsenic trioxide, 4 and rarely in patients with non-promyelocytic subtypes of acute myeloid leukemia treated with ATRA. 5 Lonafarnib (SCH66336 or Sarasart; Schering-Plough Research Institute, Kenilworth, NJ, USA) is a member of a novel class of therapeutics under investigation in hematologic malignancies, termed the farnesyl transferase inhibitors (FTIs).…”
Section: To the Editormentioning
confidence: 99%
“…Currently used in the treatment of acute promyelocytic leukemia [80,81], these agents have both been associated with the development of NCPE/ARDS in the context of ATRA syndrome. This is a life-threatening complication that occurs in a quarter of patients with acute promyelocytic leukemia who undergo remission induction treatment with ATRA or As 2 0 3 , with or without chemotherapy [82,83]. The ATRA syndrome characterizes a loosely defined constellation of signs and symptoms that primarily consist of fever and respiratory distress, but also of weight gain, peripheral edema, pleural or pericardial effusions, and hypotension [84].…”
Section: Atra Syndromementioning
confidence: 99%
“…6,7 RAS is not observed in APL patients with consolidation/maintenance therapy using ATRA, but sometimes observed during arsenic trioxide therapy for APL. 8 In both cases, hyperleukocytosis of differentiated APL cells during therapy is likely associated with RAS. 7 In addition, administration of G-CSF or hyperleukocytosis in myeloid leukemia is associated with adult acute respiratory distress syndrome, which has an indistinguishable clinical presentation from RAS.…”
Section: Introductionmentioning
confidence: 99%